CHAORDIC ENTREPRISE: SEBUAH PENGANTAR - Fransisca Mulyono (Center for Economic Studies Universitas Katolik Parahyangan, 2010)
Business environment nowadays, that becoming more and more turbulent and complex, is hard to be predicted by managements since it has the butterfly effect : the effect that brings the greater effect in other places in this world when there is a change in a certain place. Traditional organization that considering employees as an object with its rigid structure cannot adjust these rapid changes properly. It needs to be replaced by a new alternative organization: chaordic organization, i.e. an organization that combines chaos and order situation in the same time to bring changes in management as an anticipation to its environment. Chaordic organization is very important for business today because of its high appreciation on human resources making everybody in all units of organization have a high degree on autonomy and freedom, and as a result be the leading creative and innovative organization.Key words : turbulensi, kompleksitas, kreativitas, inovasi, chaordic.